Identification of serum miR-34a as a potential biomarker in acute myeloid leukemia - Huang, Yiqun; Zou, Yong; Lin, Luhui; Ma, Xudong; Chen, Hongpu (Cancer biomarkers : section A of Disease markers, 2018)
BACKGROUND: MicroRNA-34a (miR-34a), as a tumor-suppressive miRNA, has been found to induce cell apoptosis in acute myeloid leukemia (AML). However, the diagnostic and prognostic significance of miR-34a in AML remains largely unknown. OBJECTIVE: We aimed to explore its associations with clinical characteristics and prognosis of AML patients. METHODS: This study detected serum miR-34a level in 117 diagnosed AML patients and 60 control subjects by using qRT-PCR, and results were compared to clinical features and patient outcome. Since cytogenetically-normal AML (CN-AML) has a good uniformity of cytogenetics and provides a perfect platform for detection of AML biomarkers, we further analyzed miR-34a expression in 56 CN-AML subjects. RESULTS: We found that miR-34a was significantly downregulated in AML and CN-AML patients. MiR-34a underexpression was commonly observed in AML patients with intermediate/poor risk cytogenetic, and M5 subtype. ROC analysis demonstrated that serum miR-34a could well identify AML/CN-AML patients from healthy individuals. More importantly, miR-34a expression was found negatively correlated with aggressive clinical variable, and served as an independent prognostic indicator. In addition, AML/CN-AML patients with low miR-34a expression displayed shorter overall and recurrence free survival. CONCLUSIONS: Altogether, miR-34a might have an application as a diagnostic and prognostic indicator for AML patients.